2013
DOI: 10.1111/joor.12108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentist's clinical experience on treatment satisfaction of a complete denture

Abstract: The relationship between the prosthodontic experience of dentists and satisfaction of complete denture wearers remains unknown. To investigate whether a prosthodontist's clinical experience affects treatment satisfaction of a complete denture wearer. From April 2004 to July 2006, we conducted a randomised controlled trial at two centres, including 74 edentulous patients; of these, 32 and 30 were randomly allocated to the ED or ID group, respectively. All the patients rated their satisfaction with dentures, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
18

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 19 publications
0
25
0
18
Order By: Relevance
“…It is proposed that patients' decisions to continue, discontinue, or alter medical treatments are influenced by several factors including health status of the patient, prior experiences with particular treatment choices, desire to participate in treatment‐related decision making and real or anticipated beliefs regarding the effectiveness or harms of treatment . Patients' satisfaction with their medication or the services they receive has been shown to predict treatment success, continuation of pharmaceutical treatment, appropriate use of services, medical compliance and follow‐up with treatment plans . Treatment satisfaction may be a very useful outcome in clinical studies to provide insight into a patient's attitude towards hypertension treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that patients' decisions to continue, discontinue, or alter medical treatments are influenced by several factors including health status of the patient, prior experiences with particular treatment choices, desire to participate in treatment‐related decision making and real or anticipated beliefs regarding the effectiveness or harms of treatment . Patients' satisfaction with their medication or the services they receive has been shown to predict treatment success, continuation of pharmaceutical treatment, appropriate use of services, medical compliance and follow‐up with treatment plans . Treatment satisfaction may be a very useful outcome in clinical studies to provide insight into a patient's attitude towards hypertension treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ambiguous results on satisfaction have been found concerning the effect of anatomic and physiological parameters and technical denture quality . The clinical experience of the treating or attending dentists, the relationships between patients and practitioners as well as the demographic and psychological profile of patients have also been reported to play a role . Instead of one single factor, interaction of psychological, biological, anatomical, and technical elements seemed to determine patient satisfaction …”
mentioning
confidence: 99%
“…10,23,27,[29][30][31][32][33][34] The clinical experience of the treating or attending dentists, the relationships between patients and practitioners as well as the demographic and psychological profile of patients have also been reported to play a role. 10,26,[35][36][37][38][39][40][41][42] Instead of one single factor, interaction of psychological, biological, anatomical, and technical elements seemed to determine patient satisfaction. 16,43 For dental clinicians, those factors might be considered most relevant that can be detected before starting the treatment without being too obtrusive.…”
mentioning
confidence: 99%
“…Regarding the result that related the relation between preparation of DSs for the execution of the various phases and the lower frequency of failures and less difficulties, the study by Kimoto et al 21 showed Rev Odontol UNESP. 2017 Nov-Dec; 46(6): 336-342…”
Section: Discussionmentioning
confidence: 99%